Brachydactyly type C associated with shortening of the hallux. Issue 5 (May 1992) - Rowe-Jones, J M; Moss, A L; Patton, M A
Abstract : A four generation autosomal dominant pedigree of brachydactyly type C is presented with its radiological features. The hands and feet were similarly affected. All the subjects showing these changes had shortening of the big toes and, in addition, had cupped ears.